2022
DOI: 10.3390/cells11152365
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers Related to M2 Macrophage Infiltration in Alzheimer’s Disease

Abstract: Many studies have demonstrated that neuroinflammation contributes to the onset and development of Alzheimer’s disease (AD). The infiltration of immune cells in the brain was observed in AD. The purpose of the present study was to verify potential mechanisms and screen out biomarkers related to immune infiltration in AD. We collected the expression profiling datasets of AD patients and healthy donors from the NCBI’s Gene Expression Omnibus (GEO) database. We confirmed that immune-related mechanisms were involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Studies have shown that both microglia and astrocytes, as well as peripheral immune cells, are involved in neuroinflammation associated with AD ( Leng and Edison, 2021 ). Therefore, we investigated immune infiltration in AD, we found that M2 macrophages’ infiltration was significantly increased in AD, which is consistent with previous study ( Lin et al, 2022 ). In addition, neutrophils and monocytes were also upregulated in AD.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that both microglia and astrocytes, as well as peripheral immune cells, are involved in neuroinflammation associated with AD ( Leng and Edison, 2021 ). Therefore, we investigated immune infiltration in AD, we found that M2 macrophages’ infiltration was significantly increased in AD, which is consistent with previous study ( Lin et al, 2022 ). In addition, neutrophils and monocytes were also upregulated in AD.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, this methodology is more of a holistic methodology that measures the co-expressed gene modules among samples and explores the linkages between these modules and sample traits. The performance of WGCNA in hub discovery for AD and other neurological disorders was well supported by the literature (Mukherjee, 2021;Lin et al, 2022). However, we must also realize that there are limitations in WGCNA analysis: 1.…”
Section: Discussionmentioning
confidence: 73%
“…A variety of immune cells were signi cantly in ltrated in Cluster 2, and multiple biological processes related to synapse formation were signi cantly upregulated in Cluster 2. M2 macrophages have signi cant anti-in ammatory properties and can improve cognitive dysfunction in AD model mice [24], and increased synapse formation is associated with improved cognitive function [25]. Based on this, we speculate that the AD process of Cluster 2 patients may be suppressed, resulting in a better prognosis.…”
Section: Discussionmentioning
confidence: 86%